The prevalence of endophytic bacteria in plants of Trans-Ili Alatau (Experimental biology, 2015)
This paper shows that the cells of the root system of plants studied various family are the most favorable for the body of the symbiotic existence of endophytic bacteria. The results showed that endophytic bacteria reservingconstantly present within the plant tissues . The optimal culture media for the cultivation of endophytic bacteria. All strains have a good development environment for the IPA and Saburo . Determined that the optimal carbon source for the cultivation of endophytic bacteria is glucose . Among the organic nitrogen sources for further culturing endophytic bacteria is favorable peptone
Keywords: endofitny bacteria; plant; nutrient medium; peptone; glucose